Blind fall - Rice, Christopher; Weller, Frederick (New York : Audioworks, 2008)
Disgraced after a split-second decision nearly kills his marine captain, Iraq war veteran John Houck struggles to redeem himself in his captain's eyes and stumbles on a horrifying murder scene that wrongfully implicates the captain's partner.
Unabridged.
Compact discs.
Read by Frederick Weller.
Keywords: Marines; Gays in the military; Honor; Revenge; Murder; Audiobooks